Case Report: X-linked agammaglobulinemia with progressive neurodegeneration from immunological to neurological implications - Chen, Xiaoyi; Gu, Hao; Piao, Yurong; Ma, Yanli; Zhao, Yiran; Mao, Huawei; Wang, Yuan; Deng, Jie (Frontiers in Immunology, 2025)
BackgroundX-linked agammaglobulinemia (XLA) is a rare disorder associated with defective B-lymphocyte differentiation, also known as circulating B-cell deletion or deficiency, reduced levels of all serum immunoglobulin isoforms, and a lack of specific antibody production. XLA has rare neurological complications but has a refractory course and poor prognosis. Here, we report a case of XLA due to a Bruton tyrosine kinase gene variant with progressive neurodegeneration.Case descriptionWe describe a boy with XLA who had recurrent infections since infancy and, after diagnosis was confirmed by genetic testing, was started on regular intravenous immunoglobulin at the age of 5 years. However, after a second episode of suspected meningitis at the age of 4.9 years, he developed motor and cognitive deterioration, becoming unable to sit, walk, eat or speak after 8 months, with frequent tremors and multiple seizures, and died of respiratory failure at the age of 7 years. Magnetic resonance imaging showed progressive whole brain atrophy. Combined with a mild lymphocytic inflammation of the cerebrospinal fluid, we suspected a chronic active infection of the central nervous system, but it was difficult to confirm our suspicion by serological testing due to the inability to produce neutralizing antibodies.ConclusionsSevere progressive neurodegeneration in XLA is rare. With this case we would like to discuss the difficulties in diagnosing infection in patients with XLA and the role of autoimmune mechanisms in the development of neurodegeneration.